Masculinity as a barrier to men's use of HIV services in Zimbabwe - Mupambireyi Zivai; Madanhire Claudius; Campbell Catherine; Skovdal Morten; Nyamukapa Constance; Gregson Simon (BMC, 2011)
Abstract Background A growing number of studies highlight men's disinclination to make use of HIV services. This suggests there are factors that prevent men from engaging with health services and an urgent need to unpack the forms of sociality that determine men's acceptance or rejection of HIV services. Methods Drawing on the perspectives of 53 antiretroviral drug users and 25 healthcare providers, we examine qualitatively how local constructions of masculinity in rural Zimbabwe impact on men's use of HIV services. Results Informants reported a clear and hegemonic notion of masculinity that required men to be and act in control, to have know-how, be strong, resilient, disease free, highly sexual and economically productive. However, such traits were in direct conflict with the 'good patient' persona who is expected to accept being HIV positive, take instructions from nurses and engage in health-enabling behaviours such as attending regular hospital visits and refraining from alcohol and unprotected extra-marital sex. This conflict between local understandings of manhood and biopolitical representations of 'a good patient' can provide a possible explanation to why so many men do not make use of HIV services in Zimbabwe. However, once men had been counselled and had the opportunity to reflect upon the impact of ART on their productivity and social value, it was possible for some to construct new and more ART-friendly versions of masculinity. Conclusion We urge HIV service providers to consider the obstacles that prevent many men from accessing their services and argue for community-based and driven initiatives that facilitate safe and supportive social spaces for men to openly discuss social constructions of masculinity as well as renegotiate more health-enabling masculinities.